Penerapan Kebijakan Pemungutan Retribusi Jasa Umum Atas Pelayanan Kebersihan di Kelurahan Duren Tiga Kota Administratif Jakarta Selatan - Alifia Inggriani; Irawati (Jurnal Ilmu Administrasi Publik, 2026)
This study evaluates the implementation of sanitation service fee collection in Duren Tiga, South Jakarta, based on Local Regulation No. 1 of 2024. Using a descriptive qualitative method with interviews, observations, and documentation, the study applies Merilee S. Grindle’s policy implementation theory. Findings reveal that although the policy has a strong legal basis, its implementation remains suboptimal due to low public compliance, limited resources, weak inter-agency coordination, minimal socialization, and the absence of clear sanctions or incentives. The study concludes that the policy is in place but not yet effective, and recommends strengthening implementers’ capacity, increasing public awareness, and adopting digital payment systems to improve performance. Keywords Policy Implementation, Retribution Revenue, Public Services, Cleaning Services, Duren Tiga Subdistrict, Jakarta